2016
DOI: 10.6004/jnccn.2016.0060
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Prostate Cancer Early Detection, Version 2.2016

Abstract: The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Prostate Cancer Early Detection provide recommendations for prostate cancer screening in healthy men who have elected to participate in an early detection program. The NCCN Guidelines focus on minimizing unnecessary procedures and limiting the detection of indolent disease. These NCCN Guidelines Insights summarize the NCCN Prostate Cancer Early Detection Panel's most significant discussions for the 2016 guideline update, which included iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
257
0
16

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(275 citation statements)
references
References 67 publications
2
257
0
16
Order By: Relevance
“…The criteria for men to undergo prostate biopsy include prostate-specific antigen (PSA) >4 ng/mL and/or positive digital rectal examination (DRE) [3]. Because of low sensitivity of ultrasound to prostate tumor, ultrasound-guided prostate biopsies are generally mapping all around the prostate without targets [4].…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for men to undergo prostate biopsy include prostate-specific antigen (PSA) >4 ng/mL and/or positive digital rectal examination (DRE) [3]. Because of low sensitivity of ultrasound to prostate tumor, ultrasound-guided prostate biopsies are generally mapping all around the prostate without targets [4].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] An algorithm has been suggested to identify high-risk patients based on their family history, digital rectal examination results and ethnicity. 39 In the current study, while the overall mortality trend was found to have increased over the study period, there was a reduction in certain years, perhaps due to inconsistencies in the data collection. Temporarily rising trends may be due to the improved reporting and registration of deaths.…”
Section: Resultsmentioning
confidence: 46%
“…The NCCN guidelines do acknowledge that although mpMRI prior to initial biopsy is not routinely recommended, there is a growing body of evidence outlining its possible benefit and hint that a formal recommendation is imminent [30]. The EAU guidelines panel recently published a meta-analysis examining the NPV of mpMRI prior to initial biopsy and concluded that although there is potential for the test to be used as a triage for biopsy, it is still not sufficiently accurate at the present [31].…”
Section: Current Guideline Recommendationsmentioning
confidence: 99%